Genetic and phenotype recovery of Ananas comosus var. MD2 in response to ionizing radiation - Siyuan, Ma; Mohd Raf, Anis Norsyahira; Rosli, Muhamad Afiq; Mohd Zain, Nurul Amalina; Ibrahim, Mohd Hafz; Karsani, Saiful Anuar (Springer, 2023)
Due to their sessile nature, plants are exposed to various environmental stressors such as exposure to high levels of harmful ultraviolet (UV), ionizing, and non-ionizing radiations. This exposure may result in various damages, ranging from DNA and chromosomal aberrations to phenotypic abnormalities. As an adaptation, plants have evolved efficient DNA repair mechanisms to detect and repair any damage caused by exposure to these harmful stressors to ensure their survival. In this study, the effects of gamma radiation (as a source of ionizing radiation) on clonal Ananas comosus var. MD2 was evaluated. The morphology and physiology of the clonal plantlets before and after exposure to gamma radiation were monitored at specific time intervals. The degree of genetic variation between the samples pre- and post-irradiation was also analyzed by using inter-simple sequence repeat (ISSR) markers. The resulting data revealed that the heights of the irradiated plantlets were significantly reduced (compared to control), but improved with the recovery period. Irradiated samples also exhibited relatively good photosynthetic efficiency that further improved as the plantlets recover. These observations were supported by the ISSR analysis, where the genetic dissimilarities between the irradiated samples and control were reduced by 0.1017, after 4 weeks of recovery. Overall, our findings suggested that the phenotype recovery of the clonal A. comosus var. MD2 plantlets was contributed by their ability to detect and repair the DNA lesions (as exemplified by the reduction in genetic dissimilarity after 4 weeks) and hence allow the plantlets to undergo phenotype reversion to normal plant stature.